Telesna dejavnost in zdravje žensk v pomenopavzi - Radoš, Maja (Obzornik zdravstvene nege, 2014)
Introduction: Postmenopausal estrogen deficiency is associated with a number of health conditions, including cardiovascular disease, osteoporosis, depression and urinary incontinence. The purpose of the study is to discuss the information retrieved from professional and scientific sources addressing the interaction of physical activity and cardiovascular and vasomotor system, genitourinary and connective tissues as well as mental health in women in postmenopause. Methods: Literature review was carried out manually and via electronic databases COBIB.SI, PubMed, CINAHL, EMBASE and in Cochrane Library register. The literature search was limited to publications in the Slovene, English and other languages where the texts were accompanied by an abstract in English. The study was limited to the literature published from January 2000 till December 2012. According to eligibility criteria, 11 randomised controlled trials were included into the review, thematically divided into five groups. Results: It has been established that regular physical activity has a positive influence on the symptoms resulting from the estrogenic deficiency in postmenopausal women. Physical activity exerts a positive effect on cardiovascular system, mental health, urine incontinence and osteoporosis while its impact on vasomotor symptoms remains unclear. Discussion and conclusion: Postmenopausal women are advised to perform regular and moderate aerobic exercises which should be included in the preventive health programs attended by this population of women. Further research is necessary to clearly determine the impact of physical activity on vasomotor symptoms in women in postmenopause.
Keywords: cardiovascular disease; cardiovascular diseases; depresija; depression; hot flushes; kardiovaskularne bolezni; osteoporosis; osteoporoza; pomenopavza; telesna dejavnost; urinary incontinenc; urinska inkontinenca; vročinski oblivi; woman; ženske